Alpha Mangostin Inhibits the Proliferation and Activation of Acetaldehyde Induced Hepatic Stellate Cells through TGF-β and ERK 1/2 Pathways - Novriantika Lestari; Melva Louisa; Vivian Soetikno; Averina Geffanie Suwana; Putra Andito Ramadhan; Taufiq Akmal; Wawaimuli Arozal (Journal of Toxicology)
Liver fibrosis is characterized by excessive accumulation of extracellular matrix in chronic liver injury. Alcohol-induced fibrosis may develop into cirrhosis, one of the major causes of liver disease mortality. Previous studies have shown that alpha mangostin can decrease ratio of pSmad/Smad and pAkt/Akt in TGF-β-induced liver fibrosis model in vitro. Further investigation of the mechanism of action of alpha mangostin in liver fibrosis model still needs to be done. The present study aimed to analyze the mechanism of action of alpha mangostin on acetaldehyde induced liver fibrosis model on TGF-β and ERK 1/2 pathways. Immortalized HSCs, LX-2 cells, were incubated with acetaldehyde, acetaldehyde with alpha mangostin (10 and 20 μM), or alpha mangostin only (10 μM). Sorafenib 10 μM was used as positive control. LX-2 viability was counted using trypan blue exclusion method. The effect of alpha mangostin on hepatic stellate cells proliferation and activation markers and its possible mechanism of action via TGF-β and ERK1/2 were studied. Acetaldehyde was shown to increase proliferation and expression of profibrogenic and migration markers on HSC, while alpha mangostin treatment resulted in a reduced proliferation and migration of HSC and decreased Ki-67 and pERK 1/2 expressions. These findings were followed with decreased expressions and concentrations of TGF-β; decreased expression of Col1A1, TIMP1, and TIMP3; increased expression of MnSOD and GPx; and reduction in intracellular reactive oxygen species. These effects were shown to be dose dependent. Therefore, we conclude that alpha mangostin inhibits hepatic stellate cells proliferation and activation through TGF-β and ERK 1/2 pathways.